How do food bloggers and PR practitioners in the hospitality sector view their relationships? A UK perspective - Yeomans, Liz; Baxter, Hannah (Instituto de Investigación en Relaciones Públicas, 2014)
Bloggers are increasingly viewed by public relations practitioners as important influencers within the online media environment, yet research that explores relationships between bloggers and PR practitioners, particularly in the UK, is relatively limited. This paper reports on findings from a small-scale, in depth qualitative study of food blogger-practitioner relationships within the hospitality sector in the UK. The study explored why bloggers write about their restaurant experiences and how they view their relationships with PR professionals; while PR practitioners were questioned about their relationships with bloggers and the influence bloggers are having on PR clients’ reputations. In keeping with previous research, this study found that the practitionerblogger relationship is complex. The PR practitioners interviewed within the hospitality sector viewed restaurant review bloggers as highly influential to their clients’ reputations and view the relationship as one that is built on mutual interests and trust. However, bloggers do not perceive the relationship in this light and are sceptical of PR practitioners’ motives. While bloggers had different motivations for blogging, they shared a common passion for blogging and a drive to provide reliable information and objective advice to their readers. Concerns within the blogging community were highlighted in regard to accepting incentives (free meals) from PR practitioners, and how this can be damaging to bloggers’ reputations.
¿Cómo ven su relación los bloggers de alimentos y los profesionales de relaciones públicas en el sector de la hostelería? Una perspectiva del Reino Unido
Keywords: Redes sociales; Hostelería - Relaciones públicas; Food bloggers; Hospitality public relacions; Relational practice; Emotion management